2019
DOI: 10.1108/er-03-2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Talent attributes of the Indian IT industry

Abstract: Purpose This study is a comparative organizational analysis of the four subsectors of the Indian information technology (IT) industry, namely, IT service (ITS), business process outsourcing (BPO), software products services (SPS) and engineering and R&D (ER&D). The purpose of this paper is to empirically identify the cross-sectorial attributes, organizational characteristics and the talent best suited to it. Design/methodology/approach Data were collected using a qualitative research design with semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The second theme focusses on the work characteristics of supplier employees on employees' turnover intentions, including role clarity, workload, goals and challenging tasks (e.g. Cherian and Kamalanabhan, 2019; Luftman and Kempaiah, 2007). The third theme, often taking the supplier firms' perspective, pays more attention to identifying organisational factors that are associated with talent retention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The second theme focusses on the work characteristics of supplier employees on employees' turnover intentions, including role clarity, workload, goals and challenging tasks (e.g. Cherian and Kamalanabhan, 2019; Luftman and Kempaiah, 2007). The third theme, often taking the supplier firms' perspective, pays more attention to identifying organisational factors that are associated with talent retention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a review of existing studies identifying contextual factors influencing supplier firms' talent retention revealed an intra-organisational bias (e.g. Chawla, 2020; Cherian and Kamalanabhan, 2019). External factors such as industry background and host country culture are only sparingly addressed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The IT sector in India emerged in 1967 at Mumbai and achieved the significant growth within 1970-2000. It witnessed the start of software exports, the setting up of software technology parks along with the evolution of offshore companies and the entry of foreign multinational corporations [Cherian, Kamalanabhan, 2019].…”
Section: Russian and Indian It Sectormentioning
confidence: 99%
“…At the same time, Indian IT companies expect from the applicants a high level of technical expertise as well as professional flexibility, learning agility and customer orientation. Meanwhile, the talented professionals require from the employers not only an attractive salary and benefits, but also continuous learning, career and professional growth opportunities, challenging tasks [Cherian, Kamalanabhan, 2019]. Overall, although there is a large pool of local labor for the Indian IT industry, the competencies of most of them are still lacking by international standards [Thite, Budhwar, Wilkinson, 2014].…”
Section: Russian and Indian It Sectormentioning
confidence: 99%
“…For example, in a comparative study comparing talent management practices in India and China, researchers found that materialistic value systems paved the way for the relationships between employers and employees (Cooke et al., 2014). Studies conducted in India focused on the information technology sector (Cherian & Kamalanabhan, 2019; Naim & Lenka, 2017), and hospitality industry (Bahuguna et al., 2022), hotel industry (Gupta, 2020). Some studies were conducted on the banking industry in Bangladesh (Hosen et al., 2018), emerging market firms in Russia (Latukha, 2018), and multinational companies in Latin America (Golik & Blanco, 2022).…”
Section: Introductionmentioning
confidence: 99%